2022
DOI: 10.1007/978-3-031-18840-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter Importance of Quantum Neural Networks Across Small Datasets

Abstract: As restricted quantum computers are slowly becoming a reality, the search for meaningful first applications intensifies. In this domain, one of the more investigated approaches is the use of a special type of quantum circuit -a so-called quantum neural network -to serve as a basis for a machine learning model. Roughly speaking, as the name suggests, a quantum neural network can play a similar role to a neural network. However, specifically for applications in machine learning contexts, very little is known abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It would also be interesting to introduce different techniques to reduce the number of shots spent such as Bayesian optimization [27]. Finally, other empirical studies related to algorithm selection and configuration [51,55,[61][62][63][64][65] can be applied to Refoqus on different datasets [63,66,67].…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to introduce different techniques to reduce the number of shots spent such as Bayesian optimization [27]. Finally, other empirical studies related to algorithm selection and configuration [51,55,[61][62][63][64][65] can be applied to Refoqus on different datasets [63,66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Other applications of HQNNs in healthcare and pharmaceuticals include Refs. [37,[42][43][44][45]. Unfortunately, due to the limited availability of quantum computers and the difficulty of simulating their information processing capabilities using a classical computer, studies of QML in medicine are currently rather small in number.…”
Section: Quantum Machine Learning and Medicinementioning
confidence: 99%
“…Some of these methods provide a polynomial speedup, critical for large and complex problems where small improvements can make a big difference. Among these advantages, quantum computing specifically demonstrates benefits over classical computing across various domains, including chemistry simulations [19,20] and within the medical and healthcare industry [21][22][23][24][25]. For example, in [26], it was shown that already existing machine learning algorithms, being quantum enhanced, significantly contribute to medical science and healthcare.…”
Section: Introductionmentioning
confidence: 99%